2023
DOI: 10.37064/consilium.v9i2.13454
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Digital Literacy-Based Learning on Student Motivation and Socialization Ability

Abstract: Online learning programs require students to use digital literacy. The question is how does digital literacy affect student learning motivation, then does it also affect students' ability to socialize. The purpose of the study was to describe the level of digital literacy, learning motivation and social skills of FKIP students at Lancang Kuning University. The research methodology used is descriptive analysis with hypothesis testing using regression. The number of samples is 99 students who are drawn by total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…From the results of the Pearson correlation analysis in Table 6 and scatter plots in Figure 1, it is found that there is a significant correlation of digital literacy and learning motivation (p-value <0.01) with a correlation coefficient value of rpearson was 0.7294474 that indicates a strong correlation between digital literacy and learning motivation. This supports the opinion of Wahyuni, Novitasari, Suharni, & Reswita who said that there is a positive influence of digital literacy and learning motivation [18]. This is also supported by Pala & Başıbüyük who found that digital literacy and learning motivation, self-control also predicts students' academic achievement in learning [19].…”
Section: Learning Motivationsupporting
confidence: 81%
“…From the results of the Pearson correlation analysis in Table 6 and scatter plots in Figure 1, it is found that there is a significant correlation of digital literacy and learning motivation (p-value <0.01) with a correlation coefficient value of rpearson was 0.7294474 that indicates a strong correlation between digital literacy and learning motivation. This supports the opinion of Wahyuni, Novitasari, Suharni, & Reswita who said that there is a positive influence of digital literacy and learning motivation [18]. This is also supported by Pala & Başıbüyük who found that digital literacy and learning motivation, self-control also predicts students' academic achievement in learning [19].…”
Section: Learning Motivationsupporting
confidence: 81%